Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Kompetensi Terhadap Kinerja Guru Di SMA Negeri 13 Palembang - Yuniarti, Yuniarti (Utan Kayu Publishing, 2021)
This study aimed to determine the influence of Leadership Style, Organisational Culture and Competence of Teacher Performance at Senior High School number 13 Palembang. This Research was done during 3 (three) months included designing, executing and reporting the result. The experiment was conducted at Senior High School number 13 Palembang. In this study population was 70 people consisting of 30 people as a sample test and 40 people as a sample. Sampling in this study uses a census sampling technique that is sampling from a population as a whole. From the data-processing result know that the regression coefficient for variable of Leadership Style (X1) is equal to 0,304 with a significant level equal to 5%, regression coefficient for variable of Organisational Culture (X2) equal to 0,269 with a significant level equal to 5%, regression coefficient for variable of Competence (X3) equal to 0,422 with a significant level equal to 5%. From the research result known that the correlation coefficient for variable of Leadership Style (X1) with Teacher Performance (Y) is equal to 0,304 with a significant level equal to 5%, correlation coefficient for variable of Organisational Culture (X2) is equal to 0,269 with significant level to 5%. The correlation coefficient for variable Competence (X3) is equal to 0,422 with a significant level equal to 5%, while the value of correlation coefficient (R) is equal to 0,626 or 62,6% meaning to have a very strong relationship between the independent variable and dependent variable, also known that determination coefficient (R2) equal to 0,757 This value can be interpreted that level of influence percentage among variable of Leadership Style, Organisational Culture and Competence together to Teacher Performance is 75,70%. Equally the effective contribution of Leadership Style, Organisational Culture and Competence with Teacher Performance at Senior High School number 13 Palembang is equal to 75,70% while the rest 24,60% influenced by another variable which is not packed into this research. The implementation of this research is to suggest the Manager at Senior High School number 13 Palembang to improve continuously Leadership Style, Organisational Culture and Competence so that wittingly themselves together always try to utilize to reach the target which have been specified (Teacher Performance).